Outcome of 200 restorative proctocolectomy operations: the John Radcliffe Hospital experience - Samarasekera, D.N. (My University, 1997)
Background Restorative proctocolectomy is now the operation of choice for the definitive management of ulcerative colitis and familial adenomatous polyposis (FAP). Methods A total of 200 patients (1 17 male, 83 female) underwent restorative proctocolectomy over a 12-year period. Information in a dedicated prospective database was supplemented by chart review. Some 177 had ulcerative colitis, 13 had indeterminate colitis and seven had FAP. Pouch designs were two-loop J (12 = 142), four-loop W (n = 45) and three-loop S (n = 13). The majority (73.5 pcr cent) had a stapled ileoanal anastomosis and 139 patients had a defunctioning ileostomy. Results There were no deaths. Early morbidity (less than 30 days after operation) included 76 complications in 71 patients (35.5 per cent), of which 35 were related to the pouch itself. Long-term follow-up data were available for 196 patients at a median of 27 months. Sixteen pouches (8.0 per cent) have been excised. Mean daytime frequency was 4.5 (range 1-15). Of 175 patients with colitis, 42 (24.0 per cent) had one or more episodes of pouchitis. functional results, although variable, have generally been acceptable. Conclusion Continuous improvements in operative technique have simplified